The Short Term Earnings Management Ethic and Its Effect on Accounting Education and Corporate Perceptions - Arifah, Siti; Rizki Nugraha, Aditya (Advances in Accounting Innovation, 2024)
Objective: This study explores how students and company managers view earnings management strategies, with a particular emphasis on the moral and ethical aspects. It also looks at how these views differ according to gender. Enhancing knowledge of ethical behavior in financial reporting is the goal, and it will also guide future investigations and legislative actions.Methods: A structured questionnaire consisting of twenty items with ratings on a five-point Likert scale was used in a descriptive research design. There were 700 participants in the sample, 150 of whom were business managers and the remaining 550 were students from Indonesian universities. To evaluate variations based on group and gender, distribution of frequencies, means, and ANOVA were used to examine the data.Findings: Findings show that opinions of earnings management techniques varied significantly between the sexes, with men typically viewing aggressive tactics with less leniency. The study revealed that activities having more financial consequences, such as postponing costs or adjusting reserves, are subject to more scrutiny. Relationships between gender and behavior are consistent with contemporary empirical data and theoretical models such as the Concept of Planned Behavior.Novelty: This research adds to the current conversation about the ethics of finance and the effectiveness of regulatory regimes by offering fresh perspectives on the ways in which gender and certain earnings management techniques affect moral reasoning.Theory and Policy Implications: The results emphasize the necessity of customized ethical education and policy modifications to tackle gender disparities in perspectives. Future studies on the relationship between gender, organizational culture, and financial ethics should be conducted in order to provide more useful ethical guidelines and procedures for financial reporting.